The Impact of Tourism on The Local Culture of Misool, Raja Ampat, Southwest Papua - Abdul Halim Soltief; Karmila Sinen; Sofyan Muhamad (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This research aims to analyze the influence of tourism on local culture in Misool Island, Raja Ampat, Southwest Papua. Misool is an area with very high natural and cultural tourism potential, but it also faces challenges in preserving the authenticity of local culture amidst the growth of the tourism industry. This research uses a descriptive qualitative approach through a systematic literature review with thematic analysis, conducted by examining various academic sources, government reports, and relevant previous research findings. Thematic analysis is used to identify, group, and interpret the main themes related to the impact of tourism on local culture. The research results indicate that tourism provides positive impacts in the form of increased cultural preservation awareness and community welfare but also has the potential to cause cultural commodification and social change if not managed sustainably. This research emphasizes the importance of community-based tourism management, conservation, and sustainability so that the balance between economic, cultural, and environmental aspects can be maintained.